DEVELOPMENT A DAILY NUTRITIONAL ADEQUACY BALANCE IDENTIFICATION SYSTEM AS AN EFFORT TO PREVENT MALNUTRITION - Abidatul Izzah; Daniel Swanjaya; Kunti Eliyen (LPPM Nusa Mandiri, 2024)
Malnutrition is a deficiency, excess or imbalance in a person's energy and nutritional intake. Malnutrition can occur when a person has too much or too little food and important nutrients in their body. The Ministry of Health, Indonesia, has campaigned for food consumption that complies with balanced nutrition guidelines under the slogan